The effect of the leader’s personality on the emotional balance (mental and motor) of the old football players - Trif , Atallah (sports creativity, 2025)
The study aimed to find out the effect that the communicative personality to the leader has on the emotional mental balance on the football players in the state of Laghouat, namely the teams of « Etihad Aflou and Etihad Hassi Raml who are active in the third depatement of amateurs, in addition to knowing the effect that the communicative personality of the leader has on the emotional balance of movement among football players. Each of the “Etihad Aflou and Hassi Rmel team”. The study sample consists of 45 players from the two teams, and the descriptive approach has been relied upon, and the results of the study showed the validity of the general hypothesis that indicates the existence of an effect of the communicative personality of the leader on emotional